2015
DOI: 10.1007/s00216-015-8546-0
|View full text |Cite
|
Sign up to set email alerts
|

The current preference for the immuno-analytical ELISA method for quantitation of steroid hormones (endocrine disruptor compounds) in wastewater in South Africa

Abstract: The availability of national test centers to offer a routine service for analysis and quantitation of some selected steroid hormones [natural estrogens (17-β-estradiol, E2; estrone, E1; estriol, E3), synthetic estrogen (17-α-ethinylestradiol, EE2), androgen (testosterone), and progestogen (progesterone)] in wastewater matrix was investigated; corresponding internationally used chemical- and immuno-analytical test methods were reviewed. The enzyme-linked immunosorbent assay (ELISA) (immuno-analytical technique)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…For these reasons, alternative immuno-analytical methods for rapid detection of EDCs such as enzyme-linked immunosorbent assay (ELISA) and immunosensors were developed in the last years [107]. The ELISA method was successfully employed for the quantification of nonylphenol (LOD of 6 ng/L [95]), bisphenol A (LOD range 30-80 ng/L [96]), and hormones with good sensitivity (LOD of 0.2-5 ng/L for E2), accuracy (mean recovery 96%), and precision (RSD 7-10) [108]. These immuno-analytical methodologies have high sensitivity, cost effectiveness and simplification but employ bioantibodies that are unstable and require a long time to be prepared [109].…”
Section: Analytical Methodologies For Edc Detectionmentioning
confidence: 99%
“…For these reasons, alternative immuno-analytical methods for rapid detection of EDCs such as enzyme-linked immunosorbent assay (ELISA) and immunosensors were developed in the last years [107]. The ELISA method was successfully employed for the quantification of nonylphenol (LOD of 6 ng/L [95]), bisphenol A (LOD range 30-80 ng/L [96]), and hormones with good sensitivity (LOD of 0.2-5 ng/L for E2), accuracy (mean recovery 96%), and precision (RSD 7-10) [108]. These immuno-analytical methodologies have high sensitivity, cost effectiveness and simplification but employ bioantibodies that are unstable and require a long time to be prepared [109].…”
Section: Analytical Methodologies For Edc Detectionmentioning
confidence: 99%
“…The increasing concentrations of steroid hormone residues in various matrices in the environment is proof that even with the bans that are currently in place, their increased application is still predominant (Table 1). In general, global studies have shown that these hormones are frequently detected in waste and surface waters [9,29,[32][33][34][36][37][38][39][40][41][42]. The detection of steroid hormones in the environment has been reported to differ from country to country (Table 1).…”
Section: Global Concentration Levels Of Hormonesmentioning
confidence: 99%
“…In some cases, their concentrations within the same country also differ depending on the regions or provinces. For example, in South Africa, maximum concentrations for estradiol of 7133 ng/L were detected in wastewaters from Gauteng Province [42], while concentrations of up to 2000 ng/L were reported in KwaZulu Natal Province for estrone (E1), 17-βestradiol (E2), estriol (E3), 17-α-ethinylestradiol (17-α-EE2), androgens, and progestogens (PRO) [9]. Olatunji et al [45] reported concentrations ranging from 600 to 45,500 ng/L for E2 and E3 in surface water around animal farms in Western Cape.…”
Section: Global Concentration Levels Of Hormonesmentioning
confidence: 99%
See 1 more Smart Citation
“…Before constructing a strip test to meet the limit requirement, a sensitive and highly specific antibody resistant to matrix interference is needed. Many enzyme-linked immunosorbent assay (ELISA) have been developed to measure testosterone levels in plasma, serum, urine and environmental samples at high parts per million levels or even lower (Al-Dujaili, 2006;Feswick et al, 2014;Kim et al, 2015;Lu et al, 2006;Manickum & John, 2015;Nash et al, 2000;Xing, et al, 2014).…”
Section: Introductionmentioning
confidence: 99%